Nye harpunfund - Andersen, Søren H. (Kuml, 1975)
New harpoon finds After the publication in KUML 1971 of the harpoons then known (1) my attention was drawn to a number of other specimens, hitherto unknown and all to be found in private collections. Notable among the new harpoons is the single-rowed specimen fig. 1, which is a casual find from Tudeå, western Zealand. Found in fresh water, it was probably used for catching large freshwater fish like salmon, pike or catfish. Apart from superficial recent damage, the harpoon is entire. The raw material is red deer antler. The surface has been scraped smooth and the base exhibits a row of distinct secondary cuts which are probably due to a change in the method of hafting during the life of the harpoon. The line hole has a biconical section. The overall length is 32.6 cm. The two decorative elements seen on the convex, smooth side in this specimen - fine lines and deeper nicks - are combined and therefore contemporaneous. The patterns consist of lines with short transverse strokes (Clark motif c), bands with transverse hatching (Clark motif f) with small triangular figures which occur here for the first time in the Danish Mesolithic, and large hatched triangles. The decoration is difficult to interpret on account of its condition; it is probably purely geometric, but the possibility that it is a stylized animal or human representation cannot be ruled out. The ornaments on the Tudeå harpoon are, with one exception, well known from previous finds. Corresponding motifs are known from both the Maglemose and Kongemose cultures, especially from the many axes of the latter, for example those from Ølby Lyng (Kemisk Værk) (25), Carstensminde (26) and Værebro Å (28). The Tudeå harpoon should on the basis of its similarity to other well-dated specimens be assigned to the later Kongemose - earliest Ertebølle culture. The disharmony between the patterns and the shape of the harpoon shows that the decoration was probably not made for the harpoon. As several instances are known of broken antler axes having been reused as raw material for harpoons, there is reason to believe that the Tudeå harpoon has been made from a decorated antler axe of the same type as the axe from Værebro, fig. 3. The harpoon was presumably made about the same time as the axe and derives from the same period, in which case it is the oldest antler harpoon known from Denmark. A comparison between the Tudeå harpoon and the later Ertebølle harpoons also shows a number of obvious differences, first and foremost with respect to dimensions, the number of barbs and their shape, the positioning of the line hole and the length of the base. The length of the Tudeå harpoon brings to mind the earlier published unfinished harpoon from the Kongemose settlement, and an unfinished harpoon of the same size is also known from the Carstensminde settlement. These few scattered finds suggest that the single-rowed harpoons underwent a typological development in the course of the Atlantic period from long (30-35 cm) harpoons with numerous short barbs, asymmetrical line hole and long base, to shorter (15-20 cm) harpoons with one or a few, large, sturdy barbs, symmetrical line hole and short base. The material is, however, still too small for definitive conclusions to be drawn. The single-rowed harpoon, fig. 5, is a single find recovered from the stone reef Rønnerne in the western Limfjord (same locality as the harpoon fig. 7). The base and point of this very well preserved specimen have been carefully smoothed. The cylindrical line hole was drilled from the convex face. The overall length is 25 cm. This harpoon does not resemble any of the certain Ertebølle harpoons, but is allied in shape to the previously published harpoon from Præstø By (44), which is also a single find. Presumably these two harpoons represent a special type or variant of harpoons of type A (33). The regular rectangular base with pronounced shoulder is not found in any of the certain Ertebølle harpoons but is known from a Neolithic harpoon from Livø Tap (fig. 8) and in the Swedish Pitted Ware harpoons. The sparse material thus seems to suggest that this variant should be assigned to one of the Neolithic cultures. The harpoon, fig. 4, stems from the same locality as the previous specimen. It is made from a large hollow bone of unidentified species and is broken at the point and base. The line hole was drilled from both sides. The overall length is 8.6 cm. This harpoon is typologically related to Ertebølle harpoons of type A (33), but differs from these in the choice of raw material - bone - which has not been noted hitherto in Ertebølle harpoons. The specimen was recovered from the sea floor with other Ertebølle artefacts, although there is no guarantee of coevality; the harpoon may indeed belong to the Ertebølle culture, but other possibilities should not be ruled out. The specimen illustrated in fig. 8 also derives from the Limfjord (48). It was recovered from the sea floor on Livø Tap, which has already yielded another published harpoon (49). The raw material of this well preserved harpoon is domestic ox (52). The surface has been scraped smooth but exhibits in several places clear traces of rough polishing, which has not been demonstrated before in Danish harpoons. The line hole has a biconical section. The overall length is 18 cm. The raw material, mode of manufacture and shape of this harpoon suggest that it should be assigned to the Neolithic. Morphological similarity to Swedish, Pitted Ware harpoons suggests that it belongs to the Pitted Ware culture whose settlements are found in large areas in the very region where the harpoon was found (51). Finally, the material has been supplemented by the demonstration of a point fragment of a roe deer harpoon (type C) from the Ertebølle settlement of Nivågård in eastern Zealand. This fragment was found in the upper part of the culture layer, which is dated to the Dyrholmen II phase. The new harpoon finds have in several respects furnished us with new knowledge of the chronological and spatial distribution of this artefact group. For the first time a harpoon has been demonstrated which belongs to the later Kongemose or earliest Ertebølle culture. The earlier indications that antler harpoons were part of the Kongemose culture repertoire seem here to be confirmed. This is an entirely new type, clearly different from those known hitherto. At the same time the hitherto youngest dated harpoon from Denmark has been demonstrated. The specimen, which probably belongs to the Pitted Ware culture, differs in shape, raw material and mode of manufacture from those known previously. It is interesting to note that the Limfjord finds, which have now been augmented with finds from the western part, seem to be grouped around Livø Tap and Rønnerne near Lemvig Fjord -both stone reefs which are still known for their many seals. As it is hardly fortuitous that there is a concentration of harpoons there, these banks must have beeen good for seal hunting in antiquity, too. Søren H. Andersen